Allogeneic Hematopoietic Stem Cell Transplantation for Congenital Immune Dysregulatory Disorders - Bakhtiar, Shahrzad; Fekadu, Julia; Seidel, Markus G.; Gambineri, Eleonora (Frontiers in Pediatrics, 2019)
Primary immunodeficiency disorders that predominantly affect immune regulation and mechanisms of self-tolerance have come into the limelight, because at least for a subgroup of monogenetic disorders, a targeted therapy has become available. Nevertheless, their management often involves the treatment of severely compromising, refractory, multi-organ autoimmunity, leading to further increased susceptibility to infections and complications of long-term immune suppressive treatment, including the risk of malignancy. While evidence for allogeneic hematopoietic stem cell transplantation (alloHSCT) as a curative treatment option for severely affected patients by this disease category accumulates, clear indications, and guidelines for alloHSCT are lacking. Predictive and stratification-relevant tools such as disease activity scores are largely missing and often there is not a consistent genotype-phenotype correlation within the same family to facilitate the decision whether to transplant or not. In this review, we provide a literature-based update on indications and outcomes of alloHSCT for congenital immune dysregulative inborn errors of immunity according to the IUIS classification 2017.